2016
DOI: 10.1088/1478-3975/13/5/055001
|View full text |Cite
|
Sign up to set email alerts
|

Slo1 regulates ethanol-induced scrunching in freshwater planarians

Abstract: When freshwater planarians are exposed to a low-percentage (0.5%-1%) alcohol solution, they display a characteristic 'drunken' phenotype. Here we show that this drunken phenotype is a mixture of cilia-mediated gliding and scrunching, a muscular-based planarian gait which we recently demonstrated to be triggered by adverse environmental stimuli. At exogenous ethanol concentrations ≥2% (v/v), planarians become gradually immobilized and ultimately die. Using RNA interference (RNAi) for targeted gene knockdown, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
5
8
0
Order By: Relevance
“…One possible explanation for these findings is that the planarian sensory system is highly sensitive to any deviation from normal and that scrunching is a default downstream response to system perturbations. However, the observed species differences demonstrate that scrunching is not always triggered, in agreement with our previous findings that ethanol, but not methanol, trigger scrunching (62). This argues that scrunching is a specific response, whose regulation, despite the progress made in this work, remains poorly understood.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…One possible explanation for these findings is that the planarian sensory system is highly sensitive to any deviation from normal and that scrunching is a default downstream response to system perturbations. However, the observed species differences demonstrate that scrunching is not always triggered, in agreement with our previous findings that ethanol, but not methanol, trigger scrunching (62). This argues that scrunching is a specific response, whose regulation, despite the progress made in this work, remains poorly understood.…”
Section: Discussionsupporting
confidence: 92%
“…Combining the results presented here with our previous studies of scrunching allowed us to partially decipher the molecular mechanisms responsible for sensing noxious stimuli in planarians. In this and our previous work, we found that TRPA1 and TRPV channels, as well as the big potassium channel SLO-1 (62), are involved in inducing scrunching in response to specific stimuli. Using RNAi, we found that some inducers are specific to one of these pathways, such as AITC and H 2 O 2 to TRPA1, while others, such as anandamide and amputation respectively, rely on potential overlapping functions of both channels or on other unidentified channels.…”
Section: Discussionsupporting
confidence: 77%
“…The majority (5/7) of the bioactive OPFRs in regenerating and adult planarians showed specific, sublethal effects on scrunching, which were not seen to the same extent in the BFRs. Scrunching is an oscillatory, musculature-driven escape gait in planarians that is induced by specific adverse stimuli such as noxious heat (Cochet-Escartin et al, 2015), but is not a generic response to all noxious environments (Cochet-Escartin et al, 2016). Although scrunching shares qualitative features, such as muscle-based motion and increased mucus secretion, with other muscle-driven body shape changes, such as peristalsis, it can be quantitatively distinguished using four characteristic parameters: frequency and asymmetry of body length oscillations, speed, and maximum elongation (Cochet-Escartin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in S. mediterranea, ethanol exposure induces the expression of a "drunken" phenotype, characterized by atypical gliding and "scrunching"; this latter behavior was found to be modulated by a specific potassium channel (Cochet-Escartin et al, 2016). In the planarian Girardia dorotocephala, ethanol displayed environmental place conditioning, pSLMs, and pharmacological synergism with cocaine, but not with nicotine (Tallarida et al, 2014).…”
Section: Ethanol Effects On Planarian Behaviormentioning
confidence: 99%